Agent-Based Modeling of Cancer Stem Cell Driven Solid Tumor Growth - Poleszczuk, Jan (Methods Mol Biol, 2016)
Computational modeling of tumor growth has become an invaluable tool to simulate complex cell–cell interactions and emerging population-level dynamics. Agent-based models are commonly used to describe the behavior and interaction of individual cells in different environments. Behavioral rules can be informed and calibrated by in vitro assays, and emerging population-level dynamics may be validated with both in vitro and in vivo experiments. Here, we describe the design and implementation of a lattice-based agent-based model of cancer stem cell driven tumor growth.